The impact of a complete nutrition diabetic formula on glycemic control and nutritional status in hospitalized patients with diabetes mellitus - Wang, Chin-Kun; Li, Ke-Xin; Sun, Sheng-Qian; Liu, Tristan-C. (Frontiers in Endocrinology, 2025)
The clinical application of specialized oral nutritional supplements (ONS) in managing hospitalized patients with diabetes mellitus necessitates rigorous evaluation of their effects on glycemic stability and nutritional parameters. This prospective study aimed to investigate the impact of a diabetes-specific ONS, Complete Nutrition Diabetic Formula, on glycemic control and key nutritional indices in diabetic inpatients. Forty adult inpatients diagnosed with diabetes mellitus requiring nutritional support were enrolled and completed the intervention. Following assessment of individual caloric requirements, participants received an average daily supplementation of 156 g (equivalent to 2.6 packs) of the Complete Nutrition Diabetic Formula over a mean duration of 29 days (range 14-67 days). Glycemic parameters, anthropometric measurements (including mid-arm circumference, MAC), and pertinent biochemical markers (including serum magnesium) were assessed at baseline and study conclusion. Post-intervention analysis showed a higher total caloric and fat intake with a lower carbohydrate share, accompanied by significant gains in mid- arm circumference (MAC), serum magnesium, and a nitrogen-balance flip from -2.7 g/day to +1.25 g/day (p < 0.05), marking a catabolic - to - anabolic shift and confirming protein repletion. Fasting plasma glucose and other biochemical indices - including serum proteins and lipid profiles - remained unchanged (p > 0.05), indicating that short-term Complete Nutrition Diabetic Formula supplementation improves key nutritional indicators without compromising glycemic control or broader metabolic stability.